MOBILE HEALTH (MHEALTH) ADOPTION: ASSESSING THE UTILIZATION OF MOBILE HEALTH APPS IN PROMOTING HEALTHY BEHAVIOURS. A BIBLIOMETRIC ANALYSIS - Faijue, Darlington David; Lashari, Dr U.G.; Aslam, Hira; Shelke, Girish Suresh (South Eastern European Journal of Public Health, 2025)
Background: The usage of mobile health-related applications (mHealth apps) has expanded in recent years, significantly impacting healthcare by promoting healthy behaviors and improving patient engagement. Objective: To map the existing literature on the engagement and implementation of mHealth apps for health behaviors, with a focus on bibliometric trends, key contributors, and influential app features. Methods: Data Sources: Web of Science Core Collection. • Inclusion Criteria: Articles in English published between January 1, 2010, and June 30, 2024. • Study Selection: A total of 987 papers, including 670 journal articles and 317 review articles, were analyzed. • Analysis: Bibliometric analysis was conducted to examine publication trends, geographic contributions, institutional impact, and key research areas. Results: Publication Trends: A sharp increase in publications was observed, peaking at 145 papers in 2023. • Geographic Distribution: The United States leads with 310 publications and 14,500 citations, followed by Europe and significant contributions from China and India. • Key Contributors: o Researchers: Dr. Lisa Brown (Johns Hopkins University), Dr. Michael Lee (University of California), and Dr. Mei Chen (Peking University). o Institutions: Johns Hopkins University leads in publication volume, while the University of California has the highest citation frequency. • Prominent Journals: Journal of Medical Internet Research, mHealth, and Digital Health. • Keywords: Mobile applications, health promotion, user engagement, behavior change, and chronic disease management. • Influential App Features: Personalized feedback, gamification, and real-time monitoring were identified as particularly impactful in promoting healthy behaviors. Conclusions: The analysis underscores the growing research interest in mHealth apps and their role in promoting sustainable health behavior change. Interdisciplinary research and international collaboration are essential to advance the effective utilization of mHealth apps further and improve health outcomes.